Slowed Compensation Responses to Altered Auditory Feedback in Post-Stroke Aphasia: Implications for Speech Sensorimotor Integration - Johnson, Lorelei Phillip (J Commun Disord, 2020)
Developing a clearer understanding of impairments that underlie the behavioral characteristics of aphasia is essential for the development of targeted treatments and will help inform theories of speech motor control. Impairments in sensorimotor integration of speech in individuals with conduction aphasia have previously been implicated in their repetition deficits. However, much less is known about the extent to which these integrative deficits occur outside of conduction aphasia and how this manifests behaviorally in areas other than speech repetition. In this study, we aimed to address these issues by examining the behavioral correlates of speech sensorimotor impairment under altered auditory feedback (AAF) and their relationship with the impaired ability to independently correct for online errors during picture naming in people with aphasia. We found that people with aphasia generate slower vocal compensation response to pitch-shift AAF stimuli compared with controls. However, when the timing of responses was controlled for, no significant difference in the magnitude of vocal pitch compensation was observed between aphasia and control groups. Moreover, no relationship was found between self-correction of naming errors and the timing and magnitude of vocal compensation responses to AAF. These findings suggest that slowed compensation is a potential behavioral marker of impaired sensorimotor integration in aphasia.